Patient and hospital characteristics associated with do-not-resuscitate/do-not-intubate orders: a cross-sectional study based on the Taiwan stroke registry - Hsu-Ling Yeh; Fang-I Hsieh; Li-Ming Lien; Wen-Hua Kuo; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Hei-Tung Yip; Cheng-Li Lin; Nicole Huang; the Taiwan Stroke Registry Investigators; et al. (BMC Palliative Care, 2023)
Abstract Background Previous studies of do-not-resuscitate (DNR) or do-not-intubate (DNI) orders in stroke patients have primarily been conducted in North America or Europe. However, characteristics associated with DNR/DNI orders in stroke patients in Asia have not been reported. Methods Based on the Taiwan Stroke Registry, this nationwide cross-sectional study enrolled hospitalized stroke patients from 64 hospitals between 2006 and 2020. We identified characteristics associated with DNR/DNI orders using a two-level random effects model. Results Among the 114,825 patients, 5531 (4.82%) had DNR/DNI orders. Patients with acute ischemic stroke (AIS) had the highest likelihood of having DNR/DNI orders (adjusted odds ratio [aOR] 1.76, 95% confidence interval [CI] 1.61–1.93), followed by patients with intracerebral hemorrhage (ICH), and patients with subarachnoid hemorrhage (SAH) had the lowest likelihood (aOR 0.53, 95% CI 0.43–0.66). From 2006 to 2020, DNR/DNI orders increased in all three types of stroke. In patients with AIS, women were significantly more likely to have DNR/DNI orders (aOR 1.23, 95% CI 1.15–1.32), while patients who received intravenous alteplase had a lower likelihood (aOR 0.74, 95% CI 0.65–0.84). Patients with AIS who were cared for by religious hospitals (aOR 0.55, 95% CI 0.35–0.87) and patients with SAH who were cared for by medical centers (aOR 0.40, 95% CI 0.17–0.96) were significantly less likely to have DNR/DNI orders. Conclusions In Taiwan, DNR/DNI orders increased in stroke patients between 2006 and 2020. Hospital characteristics were found to play a significant role in the use of DNR/DNI orders.